P-002 Mean aneurysmal flow amplitude (MAFA) ratio: predicting outcomes of flow diverting stents for brain aneurysm treatment. (22nd July 2018) - Pereira, V; Brina, O; Cancelliere, N; Bracken, J; Nijnatten, F; Radovanovic, I; Lovblad, K; Krings, T; Grunhagen, T
Abstract : The use of flow-diverting stents (FDS) for treatment has become the first-line treatment for large for intracranial aneurysms (IAs). Preliminary studies have shown that quantitative assessment of periprocedural flow diversion efficacy may predict treatment outcomes. The aim of this study was to evaluate the ability of a novel DSA-based flow assessment tool (Aneurysm Flow) to predict complete occlusion of IAs after treatment with FDS. Methods: Patients harbouring unruptured IAs and treated with FDS alone were included. Utilizing an optical flow based method, the flow assessment tool analyzed a 3D rotational angiogram and two high frame-rate DSA sequences, acquired before and after stent placement. A ratio between pre- and post-FDS flow measurements was then automatically calculated, known as the mean aneurysm flow amplitude ratio (MAFA-R). In this study the MAFA-R threshold test was refined using a larger patient population and its performance was assessed by correlating flow ratios with aneurysm occlusion status determined at 3, 6 and 12 months post-treatment. Results: We included 54 aneurysms in this study. Receiver operating characteristics (ROC) analyses were used to optimize MAFA-R thresholds predictive of complete aneurysm occlusion for the total cohort and at 12 months, 39 out of 52 aneurysms (75%) occluded; AUC=0.67, p=0.0920, threshold=0.89. For the large aneurysm subgroup (size larger than 10 mm), the results were: at 3 months, 2 out of 19 aneurysms (11%) occluded; AUC=0.97, p≤0.0001, threshold=0.64; at 6 months, 7 out of 19 (37%) occluded; AUC=0.82, p=0.00108, threshold=0.93; and at 12 months, 11 out of 18 (61%) occluded; AUC=0.91, p≤0.0001, threshold=0.89. Conclusions: Our results demonstrate that quantification of the changes in flow within the aneurysm sac pre- and post-FDS placement, using the MAFA-R, is an independent predictor of large aneurysm occlusion (>10 mm) at 3, 6 and 12 months follow-up. On the other hand, the MAFA-R threshold for the total aneurysm cohort was not significant (p=0.09) suggesting that this method is not as effective at predicting aneurysm occlusion outcomes for smaller aneurysms. Future studies validating the MAFA-R thresholds that predict large aneurysm occlusion are encouraged. Disclosures: V. Pereira: 1; C; Philips. O. Brina: None. N. Cancelliere: None. J. Bracken: 5; C; Philips. F. Nijnatten: 5; C; Philips. I. Radovanovic: None. K. Lovblad: None. T. Krings: None. T. Grunhagen: 5; C; Philips.